Exploring opportunities for action competence development through learners' participation in waste management activities in selected primary schools in Botswana - Silo, Nthalivi (Rhodes University, Faculty of Education, Department of Education, 2011)
The broader aim of this study is to probe participation of learners in waste management activities in selected primary schools in Botswana and through these activities, explore opportunities for action competence development. The study starts by tracing and outlining the socio-ecological challenges that confront children and the historical background of learner-centred education which gave rise to an emphasis on learner participation in Botswana education policy. It then maps out the development of children's participation in the global, regional and Botswana contexts by tracing the development of environmental education from early ecological and issue resolution goals of environmental education to sustainable development discourses. The focus is on policy issues and how learner participation has been represented and implemented in environmental education. The study then probes the rhetorical and normalised emphases on participation, and seeks further insight into how learners can be engaged in participatory learning processes that are meaningful, purposeful and that broaden their action competence and civic agency. The study uses the Cultural Historical Activity Theory (CHAT) methodology to build a picture of waste management activity systems in primary schools and to bring to the surface contradictions and tensions in learner participation in these activity systems. These contradictions are used to open up expansive learning participatory processes with learners using the Danish action competence framework. The expansive learning process uses action competence models that provide potential for transformative participation with learners, and new and different opportunities for learner participation. Case study research was used and conducted in the south eastern region of Botswana in three primary schools in three contexts, namely urban, peri-urban and rural. The data was largely generated through focus group interviews during workshops with children and observations of waste management activities. These two methods formed the main data generation methods. They were complemented by semi-structured interviews with teachers, and other actors in the waste management activities, learners' activities and work, learners' notes, photographs and children's drawings as well as show-and-tell explanations by learners. Content analysis and the abductive mode of inference were used to analyse data in all three case studies. Findings from the first phase of the study reveal that participation of learners in waste management activities was largely teacher-directed. This resulted in a mis-match between teachers views of what practices are necessary and important, and children's views of what practices are necessary and important in and for environmental education. Due to culturally and historically formed views of environmental education, the study reveals that teachers wanted children to pick up litter, and this was their primary environmental education concern. Learners on the other hand, identified sanitation management in the school toilets as their primary waste management concern. Teachers had not considered this an environmental education concern. Using the action competence expansive learning approach, the second phase of the study addressed this tension by opening up dialogue between teachers and learners and amongst the learners themselves through an expansive learning process supporting children's participation and action competence development. Through this teacher-learner dialogical engagement, a broader range of possibilities became available and ideas around participation were radically changed. The study further reveals that the achievement of this open dialogue provided for a better relationship within the school community. And with improved communication came better ideas to solve waste management issues that the community still face on a daily basis, such as too much litter. Newly devised solutions were practical and had a broader impact than the initial ones that teachers had always focussed on. They included mobilising the maintenance of toilets, landscaping the school premises and even re-contextualising the litter management that had always caused tensions between learners and teachers. Children seemed to be developing not only a better understanding of the environment, but also developing the ability to resolve conflict amongst themselves and with their elders. By engaging in dialogue with children, they became co-catalysts for change in the school community. This study shows that if children's participation is taken seriously, and if opportunities for dialogue exist between teachers and children, positive changes for a healthier environment can be created in schools. It reveals that children also appeared to be feeling more confident and more equipped to consider changes in their environment outside of the school community. The study further shows that participation in environmental education involves more than cognitive changes as proposed in earlier constructivist literature; it includes in-depth engagement with socio-cultural dynamics and histories in the school context, such as the cultural histories of teachers, schooling and authority structures in the cultural community of the school. The study recommends that there is need to strengthen Teacher Education programmes to develop teaching practices and support for teachers to identify ways of engaging learners' views on issues in the school in open, dialogical ways. Such Teacher Education programmes should deepen teachers' understandings of learners' zone of proximal development (ZPD), demonstrating how dialogue and scaffolding are part of a teacher's role in supporting learning. This is shown in the three case studies that form part of this study. Finally, the study also deepens insights of using the Cultural Historical Activity theory (CHAT) to shed light on issues surrounding learner participation within the socio-cultural and historical environmental education contexts of the schools. The action competence models used in the study provide a tool for revealing forms of learner participation. This tool can be used for critical reflections and monitoring of teaching practices in schools.
Keywords: Environmental education -- Botswana -- Case studies; Environmental education -- Study and teaching (Primary) -- Botswana -- Case studies; Environmental education -- Activity programs -- Botswana -- Case studies; Student-centered learning -- Botswana -- Case studies; Refuse and refuse disposal -- Environmental aspects -- Botswana -- Case studies; Active learning -- Botswana -- Case studies; Competency-based education -- Botswana -- Case studies; Teacher-student relationships -- Botswana -- Case studies